Study on field capacity and UAV operation time during aerial fertilizer spraying in rice field - Kharim, Muhammad Nurfaiz Abd.; Wayayok, Aimrun; Shariff, Abdul Rashid Mohamed; Abdullah, Ahmad Fikri; Husin, Ezrin Mohd; Mahadi, Muhammad Razif (AIP Publishing, 2023)
Fertilizer spraying to improve rice yield using an Unmanned Aerial Vehicle (UAV) is receiving a lot of interest from rice farmers due to its field operational advantages. However, operators have to rely on their flying experiences and skills to perform an effective aerial spraying over the rice field. This study aims to investigate UAV field capacity and time consumed while performing different rates and types of fertilizer for the aerial spraying operation. The spraying experiments were conducted in fields located in Sungai Besar, Selangor with an area of about 0.6 ha/field. The field capacity, flying time for aerial spraying, frequency of refilling tank, and changing the battery set were recorded and evaluated. The results showed that uniform rate fertilizer consumes most of the flying time for the spraying process thus required a higher number of batteries set and refilling procedure. Activities such as UAV flying time, refilling of the tank, and changing the battery set during the spraying procedure were associated with the volume of liquid sprayed to the field. Treatment of variable rate application (VRA) fertilizer showed faster in terms of time-consuming for the aerial spraying operation, better field capacity, less volume of liquid, and less energy to operate the UAV.